The South African Traditional Communities and Women for Rural Democracy and Land Rights - Wandile Brian Zondo (African Journal on Land Policy and Geospatial Sciences)
ABSTRACT Context and background The traditional communities of South Africa, particularly in the apartheid’s former homelands, have had to grapple with issues of the distortion of living customary law. This distortion has been exacerbated by the continued lack of meaningful public consultation with traditional communities, by the government, traditional authorities, and external parties on matters that relate to traditional governance and land administration. The rural women of South Africa have historically played a crucial role in the fight against these distortions of living customary law and for rural democracy – a traditional governance and land administration that is aligned with our constitutional democracy. However, their contributions have often been marginalised due to systemic challenges stemming from historical injustices, gender discrimination, and entrenched patriarchal practices. Nevertheless, the role of rural women has resulted in some strides toward the democratization of traditional governance and land administration. However, substantial obstacles persist, particularly within the legal and policy frameworks that remain mostly ineffective and do not adequately address the realities faced by traditional communities and their living customary laws. There is a huge legal lacuna caused by the oversights of legislatures, policymakers, and external parties: the insufficient public participation for traditional communities, the centralization of power within leadership institutions, and the perpetuation of apartheid-induced subjugations and oppressions of traditional communities by the current legislative frameworks, contrary to living customary law. Goal and Objectives: This paper seeks to affirm and pay tribute to the contributions of women, such as the late activists Constance Mogale and Sizani Ngubane, who tirelessly advocated for the rights of traditional communities and rural women. It aims to evaluate the existing challenges within the legal framework of traditional governance and land administration. The primary objectives are to highlight the critical need for legal reforms that reflect the lived experiences of traditional communities and to advocate for substantive consultations with these communities during legislative and policymaking processes. Methodology: The analysis draws on doctrinal research which involves the analysis of South Africa’s traditional governance and land administration laws, peer-reviewed journal articles, books, electronic media, government reports, and technical reports on the intersectionality of traditional governance, land rights, and rural democracy. I also draw from my experiences working as a Researcher for Natural Justice, Southern Africa Hub (NJ), and previously at the Land and Accountability Research Centre (LARC), within and with the traditional communities of South Africa. Through this analysis, the paper seeks to evaluate the status of the legislative frameworks on traditional governance and land administration, challenges, and solutions thereto. Fundamentally, it seeks to determine how can South Africa reform its traditional governance and land administration systems while ensuring that traditional communities are adequately represented in dialogues that shape their lives. Results: The paper underscores the urgent need for policies that empower traditional communities, protect informal land rights, and address gender discrimination and patriarchal structures. By advocating for inclusive legal reforms and authentic public participation, the paper posits that South Africa can establish a more equitable traditional governance system that recognises and values the vital contributions of traditional communities and rural women.